2017
DOI: 10.4184/asj.2017.11.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Gabapentin versus Pregabalin to Decrease Postoperative Pain after Lumbar Microdiscectomy: A Randomized Controlled Trial

Abstract: Study DesignRandomized controlled trial.PurposeThe purpose of this study was to compare pregabalin and gabapentin for mean postoperative visual analog score (VAS) for pain in patients undergoing single-level lumbar microdiscectomy for intervertebral disc prolapse at a tertiary care hospital.Overview of LiteraturePregabalin has a superior pharmacokinetic profile and analgesic effect at lower doses than gabapentin; however, analgesic efficacy must be established during the perioperative period after lumbar spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The epidural approach provides better early pain control, with fewer PONV events and a lower request for supplemental analgesics, suggesting that as long as patients are selected carefully, spinal anesthesia may be a safer and a more economical alternative; however, locoregional anesthesia can be precluded in some cases of coagulopathy . In recent years, researchers have focused on the use of systemic drugs combinations: our results show that gabapentinoids may have their greatest impact as part of a multimodal analgesic approach, and question the analgesic efficacy of pregabalin/gabapentin as a single drug in the treatment of postoperative pain following lumbar spine procedures, especially in a preemptive approach . As confirmed by recent meta‐analysis studies about the efficacy of pregabalin in reducing postoperative pain, several studies were found to have limitations (number of studies and sample size); therefore, a multicenter RCT is needed to accurately identify the effects and optimal dose of pregabalin for reducing acute pain after spine surgery .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The epidural approach provides better early pain control, with fewer PONV events and a lower request for supplemental analgesics, suggesting that as long as patients are selected carefully, spinal anesthesia may be a safer and a more economical alternative; however, locoregional anesthesia can be precluded in some cases of coagulopathy . In recent years, researchers have focused on the use of systemic drugs combinations: our results show that gabapentinoids may have their greatest impact as part of a multimodal analgesic approach, and question the analgesic efficacy of pregabalin/gabapentin as a single drug in the treatment of postoperative pain following lumbar spine procedures, especially in a preemptive approach . As confirmed by recent meta‐analysis studies about the efficacy of pregabalin in reducing postoperative pain, several studies were found to have limitations (number of studies and sample size); therefore, a multicenter RCT is needed to accurately identify the effects and optimal dose of pregabalin for reducing acute pain after spine surgery .…”
Section: Discussionmentioning
confidence: 90%
“…Of the 14 RCTs that evaluated systemic pharmacological therapies to prevent and treat postoperative pain after lumbar spine procedures, pregabalin was tested in 7 RCTs, nonsteroidal anti‐inflammatory drugs (NSAIDs) in 2 RCTs, and other drugs (dexamethasone, minocycline, propofol, sevoflurane, paracetamol, naproxen, ketamine, and clonidine) in the remaining 5 RCTs . Of the 7 RCTs that tested pregabalin, 4 demonstrated that pregabalin alone or in association with other drugs was more effective than placebo, 1 that it was as effective as placebo, and 2 that it was more effective than morphine in preventing postoperative pain . The 2 RCTs that tested NSAIDs showed that parecoxib, ketorolac, and etoricoxib were more effective than placebo in preventing postoperative pain .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations